PENERAPAN METODE GUIDED READING BERBANTUAN MEDIA KALENDER CERITA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA PADA MUATAN PELAJARAN BAHASA INDONESIA KELAS III MI MUHAMMADIYAH 02 PEKANBARU - Desy Susanti (Pelantar Press, 2024)
This research aims to examine the implementation of the Guided Reading Method supported by the Story Calendar Media to improve students' reading comprehension skills in Indonesian Language lessons for third-grade students at MI Muhammadiyah 02 Pekanbaru. The study is designed as a Classroom Action Research (CAR) with a qualitative and quantitative approach, conducted in two cycles to assess the effectiveness of the intervention. The subjects of the study were 30 third-grade students, consisting of 15 boys and 15 girls. Data were collected through tests, observations, interviews, and documentation. The test results showed a significant improvement in students' reading comprehension. In the first cycle, the average comprehension score was 75%, with 50% of students achieving scores above 75%. After improvements were made in the second cycle, the average score increased to 90%, with 83% of students achieving scores above 80%. The results from the observations and interviews indicated that the use of the Story Calendar Media helped students visualize the storyline and facilitated better understanding of the reading material. The Guided Reading method encouraged active participation and increased students' engagement in the learning process, especially in group discussions. In conclusion, the implementation of the Guided Reading Method with Story Calendar Media has been effective in improving students' reading comprehension skills in Indonesian Language lessons. It is recommended that teachers continue to incorporate various media to enhance students' engagement and understanding, particularly in early education settings